Channel Network Control on Seasonal Lake Area Dynamics in Arctic Deltas. Issue 7 (31st March 2020) - Vulis, Lawrence; Tejedor, Alejandro; Schwenk, Jon; Piliouras, Anastasia; Rowland, Joel; Foufoula‐Georgiou, Efi
Abstract: The abundant lakes dotting arctic deltas are hotspots of methane emissions and biogeochemical activity, but seasonal variability in lake extents introduces uncertainty in estimates of lacustrine carbon emissions, typically performed at annual or longer time scales. To characterize variability in lake extents, we analyzed summertime lake area loss (i.e., shrinkage) on two deltas over the past 20 years, using Landsat‐derived water masks. We find that monthly shrinkage rates have a pronounced structured variability around the channel network with the shrinkage rate systematically decreasing farther away from the channels. This pattern of shrinkage is predominantly attributed to a deeper active layer enhancing near‐surface connectivity and storage and greater vegetation density closer to the channels leading to increased evapotranspiration rates. This shrinkage signal, easily extracted from remote sensing observations, may offer the means to constrain estimates of lacustrine methane emissions and to develop process‐based estimates of depth to permafrost on arctic deltas. Plain Language Summary: The numerous lakes and ponds on arctic deltas emit large quantities of methane, but changes in lake area over spring and summer confound emission estimates. We studied summertime changes in lake area in two deltas over the past 20 years and found that lake area shrank at a higher rate closer to river channels on the delta. Thicker vegetation which increases water loss and a deeper unfrozen soil layer which stores more water underground closer to the channels are likely contributors to the observed higher shrinkage rates. This information can be used to improve estimates of methane emissions from lakes on arctic deltas, to monitor future changes in a warming climate, and to develop physically based models of depth to permafrost on arctic deltas. Key Points: Summertime lake shrinkage in arctic deltas is highly structured around the channel network Higher shrinkage rates closer to channels are attributed to enhanced near‐surface flow and storage as well as greater vegetation density Lake methane emission estimates on arctic deltas should account for spatially and seasonally variable lake extents to reduce uncertainty